A fresh start in ambersnail (Gastropoda: Succineidae) taxonomy: finding a foothold using a widespread species of Oxyloma - Perez, Kathryn E.; Martinez Cruz, Marco A.; Steury, Brent W.; Barker, Gary M. (European Journal of Taxonomy, 2021)
The ambersnails (Succineidae), found nearly worldwide, are considered a very challenging group to classify and identify with even genus-level identifications requiring dissection. In this study, we use mitochondrial and nuclear DNA markers, shell morphometrics, and anatomical dissection to examine fresh material collected from the type localities of two nominal species in Oxyloma (Neoxyloma). We conclude from these evidence that Oxyloma salleanum (L. Pfeiffer, 1850) and Oxyloma effusum (L. Pfeiffer, 1853) are conspecific, and accordingly reduce O. effusum to the status of junior synonymy. We present a redescription of O. salleanum.